Type II Diabetes Mellitus And Anti-Diabetic Therapy Patterns In Hospital X, Central Java - Okky Intan Mawarni; Anak Agung Indah Krisnadewi; Elsa Mahardika Putri; Anis Akhwan Dhafin; Fendy Prasetyawan (Journal Health of Indonesian, 2024)
Type 2 DM can be a risk factor for arteriosclerotic cardiovascular disease complications (coronary heart disease, stroke, and peripheral arterial disease), heart failure, chronic renal failure, and cardiovascular risk. This cross-sectional study was conducted on 100 type 2 diabetic patients who were prescribed anti-diabetic therapy. The prescription pattern was analyzed and adherence to treatment guidelines was done by comparing with the 2021 PERKENI guidelines. The results of the distribution of the characteristics of T2DM respondents at X Hospital 2022 were mostly aged> 45 years as much as 87%, the most gender was male as much as 54%, the most comorbidities were 97% of respondents, the most treatment pattern was monotherapy as much as 64%, the highest number of drugs received by patients was 81% with criteria> 5 drugs.